Knowledge representation and sharing using visual semantic modeling for diagnostic medical image databases. - Barb, A.S.
Information technology offers great opportunities for supporting radiologists' expertise in decision support and training. However, this task is challenging due to difficulties in articulating and modeling visual patterns of abnormalities in a computational way. To address these issues, well established approaches to content management and image retrieval have been studied and applied to assist physicians in diagnoses. Unfortunately, most of the studies lack the flexibility of sharing both explicit and tacit knowledge involved in the decision making process, while adapting to each individual's opinion. In this paper, we propose a knowledge repository and exchange framework for diagnostic image databases called "evolutionary system for semantic exchange of information in collaborative environments" (Essence). This framework uses semantic methods to describe visual abnormalities, and offers a solution for tacit knowledge elicitation and exchange in the medical domain. Also, our approach provides a computational and visual mechanism for associating synonymous semantics of visual abnormalities. We conducted several experiments to demonstrate the system's capability of matching synonym terms, and the benefit of using tacit knowledge in improving the meaningfulness of semantic queries.
Keywords: Collaborative environment; Computational mechanism; Content management; Content-based image retrieval; Decision making process; Decision support; Diagnostic medical image database; Evolutionary system; Image retrieval; Knowledge exchange; Knowledge exchange framework; Knowledge repository; Knowledge representation; Knowledge sharing; Medical domain; Radiologists; Semantic information exchange; Semantic query; Synonym term matching; Tacit knowledge; Visual abnormality; Visual patterns; Visual semantic modeling